A study on data protection law in Malaysia / Muhammad Habibullah Mohammad Shah ...[et al.] - Mohammad Shah, Muhammad Habibullah; Shamsuri, Mohd Afif Sham; Nawi, Nurul Azree; Mohd Azizan, Noor Syaffinaz (2011)
This paper was done to critically analyse the current situation in Malaysia with regards to the protection of personal data; particularly the Personal Data Protection Act 2010. Comparison between data protection laws as well as noted data protection instruments around the world was done in order to shed some light in the current global trend in safeguarding the rights of the privacy of their personal data. This research represents the initial effort to provide a critical analysis of the principle of data protection laws around the world as in comparing the situation in Malaysia. Since the Personal Data Protection Act 2010 was still not put in effect at the time that this paper was carried out, this research would provide a study of the possible effects and also what can be done in order to improve the Act to suit the need of all Malaysian data subjects as a whole.